Passion, Perseverance, and Performance: A Systematic Review of Grit - Sadaf Sajid, Khyzer Hayat Sukhera, Nida Yousaf, Ahmad Muqeem, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Grit, defined as perseverance and passion for long-term goals, has emergedas a significant non-cognitive attribute associated with success in academic, professional,and personal domains. Unlike intelligence, which has traditionally been considered theprimary predictor of achievement, grit incorporates persistence, sustained effort, andconsistent interests that contribute to long-term accomplishment